Reactive oxygen species in the immune system - Yang, Yuhui; Bazhin, Alexandr V.; Werner, Jens; Karakhanova, Svetlana (International reviews of immunology, 2013)
Reactive oxygen species (ROS) are a group of highly reactive chemicals containing oxygen produced either exogenously or endogenously. ROS are related to a wide variety of human disorders, such as chronic inflammation, age-related diseases and cancers. Besides, ROS are also essential for various biological functions, including cell survival, cell growth, proliferation and differentiation, and immune response. At present there are a number of excellent publications including some reviews about functions of these molecules either in normal cell biology or in pathophysiology. In this work, we reviewed available information and recent advances about ROS in the main immune cell types and gave summary about functions of these highly reactive molecules both in innate immunity as conservative defense mechanisms and in essential immune cells involved in adaptive immunity, and particularly in immune suppression.
Gesehen am 23.07.2021